Winter poem (Hearts of Space Records, 2011)
" ... features all new original songs by Rolf Lovland, with Fionnuala Sherry s violin as the trademark sound of the group. Featured singers include Moya Brennan (of Clannad) singing The Dreams, Fionnuala Gill singing All on a Christmas Morn, and Powered by Nature, with vocals by Tracey Campbell and Espen Grjotheim. All music is symphonically scored, arranged and produced by Rolf and performed by Secret Garden with the Czech National Symphony Orchestra."--Amazon.